Recognition of Call Centre as an Effective E-Student Support Service in Open Distance Learning (ODL) - Khanum, Samera; Madiha Bashir (IJLTP, 2025)
Technology has brought innovations in education systems all over the world. Call centres are for students’ facilitation in the field of open and distance learning. This study was carried out on recognition of call centre as an effective e-student support service in open distance learning (ODL). Data was collected by structured questionnaire with the help of call center director, staff of call centre and distance learner. It was conducted with the help of faculty of distance learning education, director, call centre staff and with the help of students who filled the questionnaire to define the key duties and key performance indicators they had in managing their call centre, along with how call centre was structured and functional. The purpose of this study was to see the effectiveness of call centre 200 students and 10 employees were selected from the population using random sampling technique. The data was analyzed by using descriptive statistics, mean-test and one-way ANOVA. The evaluation of answers given by call Centre staff and students questionnaire was used as a data collection tool. Results shows that, likewise student affairs, a call centre in education serves as a solution Centre which drives to resolves all sorts of matter of learner. It is considered a bridge between learner and teachers. It was concluded that without a call and support centre, the distance education process will face a lot of problems in various communication matters.